Seed priming application to increase sorghum vigor and viability of Sorghum bicolor - Retno Dwi Andayani; Aulia Dewi Rosanti (Universitas Trunojoyo Madura, 2023)
Sorghum is one of developed plants for food diversification because it caontains nutrients and has the potential to be an alternative crop. This is also supported by the advantages of sorghum such as adaptive, drought tolerant, salinity tolerant, wide adaptabiliti and lower water requirements for season compared to other commodities. Behind its advantages, soghum has low vigor and viability. Low vigor and viability cause low growth simultaneously. The uneven growth of sorghum makes fertilizer application and harvesting more difficult. It also increases labor costs because maintenance and harvesting cannot be done at the sam time. This can be overcome by seed priming. The purpose of seed priming is to increase the germination rate, percentage of gemination, simultaneity of growth and germination speed. This research was conducted in a controlled temperature room using a factorial randomized block design. First factor is 3 sorghum varieties and the second factor is kind of solvent (Water, Hot water, KNO3, and Ascorbic acid). The result showed that there was an interaction between sorghum varieties and kind of solvent. KNO3 gives optimal results in all sorghum varieties compared to other ingredients.